Development Of Students' National And Public Skills In Managing The Educational Process - Shakirova Moxinur Botirjonovna (Zien Journals, 2024)
This article presents thoughts and opinions on the development of students' national and general cultural skills in the educational process.
Keywords: national; universal; competence